Unemployment Insurance in the United States: Analysis of Policy Issues 1997
DOI: 10.17848/9780585338408.ch8
|View full text |Cite
|
Sign up to set email alerts
|

Financing Benefit Payments

Abstract: Unemployment insurance in the United States : analysis of policy issues / Christopher J. O'Leary, Stephen A. Wandner, editors. p. cm. Includes bibliographical references and index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although somewhat dated, a large amount of research exists on the effects of varying an employer's UI tax rate according to that employer's unemployment risk. Almost all of these studies have found that altering the degree of experience rating has a significant impact on temporary cyclical and seasonal layoffs (Levine )…”
Section: Relevance Of Experience Rating Ui Taxes Todaymentioning
confidence: 99%
“…Although somewhat dated, a large amount of research exists on the effects of varying an employer's UI tax rate according to that employer's unemployment risk. Almost all of these studies have found that altering the degree of experience rating has a significant impact on temporary cyclical and seasonal layoffs (Levine )…”
Section: Relevance Of Experience Rating Ui Taxes Todaymentioning
confidence: 99%
“…3 Tax rates vary geographically, with some states levying higher tax rates than others. 4 Moreover, tax rates vary across firms within a state, as most all states base the unemployment insurance tax rate an employer must pay on the firm's past unemployment experience, and the states differ by the degree of this experience rating (see Levine 1997;and Topel 1990).…”
Section: Introductionmentioning
confidence: 99%